On the application of trapped vortices in motorsport application for improved aerodynamic performance using passive and active flow controls - Ng, Ming Kin; Teschner, Tom-Robin (Society of Automotive Engineers (SAE), 2025)
New regulations introduced by the Fédération Internationale de l’Automobile (FIA) for the 2026 Formula 1 season mark the first instance of active flow control methods being endorsed in Formula 1 competition. While active methods have demonstrated significant success in airfoil development, their broader application to grounded vehicle aerodynamics remains unexplored. This research investigates the effectiveness of trapped vortex cavity (TVC) technology in both active and passive flow controls, applied to a NACA0012 airfoil and an inverted three-element airfoil from a Formula 1 model. The investigation is conducted using numerical methods to evaluate the aerodynamic performance and potential of TVC in this paper. In the single-airfoil case, a circular cavity is placed along the trailing edge (TE) on the suction surface; for the three-element airfoils, the cavity is positioned on each airfoil to determine the optimum location. The results show that the presence of a cavity, particularly with active flow control, significantly improves the lift-to-drag ratio (CL/CD) for both the single airfoil and the three-element airfoils. A maximum enhancement of 1160% was recorded for the single airfoil, while the three-element airfoils saw an improvement of 313% compared to their original configurations. However, when the TVC was placed in positions other than the TE of the mid-airfoil, a performance reduction was observed, even with active blowing applied. The passive flow control approach, which requires no additional energy input, yielded a modest improvement of 3.52% for the NACA0012 airfoil. However, passive control underperformed due to unstable vortex interactions with each airfoil element for the inverted three-element airfoil case. Even with optimal placement and geometrical modifications, the maximum CL/CD ratio for passive control was only 96% of the original CL/CD of the unmodified three-element airfoils, suggesting that passive flow control is less effective here compared to active flow control.
Technical paper
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; 4002 Automotive engineering; 4014 Manufacturing engineering